Effect of m a tings among broiler breeder parent groups of different body weight on broiler performance :i. performance of broiler breeders - Süleyman Dere; M.Alı Tekeş (Eurasian Journal of Veterinary Sciences)
The purpose of this study is 1o determine the relationships belween body weight and age ol sexual maturity in broiler breeders and to determine the effects of housing together male and female broiler parents with different body weight at 22 weeks old age dunng production period on mortality, egg production, egg weight, hatchablity, fertility. As the research material. 778 Avian female and 116 Peterson male broiler breeders were used Pareni male and female chickens were separately divided into three base body weight groups called light, middle and heavy al 22 weeks old age Separately three body weight subgroups which have almost similar variance and average values were obtained from base body weight groups by using sensitive sampling method Six male and 64 female broiler breeder parent chickens obtained from bodyweighl subgroups were housed in 9 pens during production period, Egg production percentage, egg weight, halchability, fertility, age at sexual maturity of broiler breeder chicken groups were determined. Age at onset ot lay ot Hh (Light male X light lemale), Ha, Ho. Ah. AafHeavy male x heavy female), Ao, Oh Oa and OofMiddle male x middle female) broiler breeder female groups were determined as 186, 179. 181, IBS 173 181. 184, 176, and 180 days, respectively. There were no statistically significant dilferences among broiler breeder parent groups in respects of average production period egg production percentage, egg weight, fertility and hatc-hability As a result. il can be said that there were need to investigate the effect of body weight trait ot different mating groups at sexual maturity age in broiler breeders on the performance of then offsprings.